Promoting Clinical Skills Acquisition and Proficiency Using Video Modelling Among Medical Students in Preclerkship - Agbarakwe, Haret Akudo (European Scientific Journal, ESJ, 2018)
This study was designed to make bare the importance of a proficiency driven curriculum, the need to foster self -directed and self- motivated learners hence the study investigated the factors influencing the acquisition of clinical skills and skills proficiency in preclerkship clinical education using video modelling among medical students in MacArthur Clinical Skills Laboratory (MCSL). It adopted the ex-post facto design. The population of the study was three hundred and eight(308) 4 th and 5 th year medical students who took the course Introduction to Clinical Medicine (ICM). Four research questions and four hypotheses guided the study. The instrument titled clinical skills acquisition through video modelling questionnaire (CSATVMQ) was developed and used to collect data. The reliability of the instruments was established using the Cronbach Alpha method of internal consistency. The reliability coefficients of the sub scales of CSATVMQ were 0.57, 0.84, 0.86, 0.95, respectively for self- directed learning, clinical skills acquisition, frequency of visitation and proficiency. Simple percentage was employed for analyzing the research questions while the hypotheses were tested using the chi-square. The findings established that the utilization of video modelling technique for the promotion of clinical skills acquisition and proficiency was not dependent on gender, academic level and age of medical students, also further test with lambda ( λ) indicated no relationship with a λ value of 0.0 between the dependent and independent variables studied. The researcher therefore recommend that College of Health Sciences, University of Port Harcourt should allocate more time in their Faculty lecture timetable to provide students with adequate practice hours and feedback sessions while enforcing it as a compulsory teaching and learning technique to enhance proficiency and self –evaluation of learnt skills during preclerkship clinical training.